Fundamental rights and the implementation of a bill of rights in South Africa1 - Niekerk, P. J. van (Koers, 1989)
In the title of this article reference is made to fundamental rights and not human rights because it is my contention that human rights should be seen as only one category of fundamental rights. In the first section an overview is given of the human and group rights discussion in South Africa and in the second section different strategies regarding the introduction of a bill of rights in South Africa are considered. Against the background of these discussions in the third section, attention is given to the different categories of fundamental rights which could be meaningfully protected in the constitutions of developing states. In the fourth section the importance of the creation of a fundamental rights legal culture in South Africa is reviewed against the backdrop of the constitutional histories of England and France.